Multisystemic Sarcoidosis Presenting With Leg Ulcers, Pancytopenia, and Polyserositis Was Successfully Treated With Glucocorticoids: A Case Report and Literature Review - Qiao, Xin; He, Shan; Altawil, Abdullah; Wang, Qiu-yue; Kang, Jian; Li, Wen-yang; Yin, Yan (Frontiers in Medicine, 2022)
Introduction Sarcoidosis is a chronic granulomatous disease of unknown etiology. A variety of studies have pointed out that almost every part of the body can be affected, but it most often affected the lungs and intrathoracic lymph nodes. However, cases of sarcoidosis involving multiple organs in one patient are rarely reported. We describe a unique case of sarcoidosis, which was characterized by multiorgan involvement, including leg ulcers, splenomegaly, pancytopenia, and polyserositis. Glucocorticoids were effective during the treatment of the above lesions. This case highlights the diversity of clinical manifestations of sarcoidosis and emphasizes the importance of its differential diagnosis and the periodical follow-up. These are crucial to physicians in the diagnosis and treatment of sarcoidosis. Main Symptoms and Important Clinical Findings A 30-year-old male complained about intermittent fever 3 years ago. A computed tomographic scan of the chest showed lymphadenopathy in the mediastinum and hilar regions. Routine blood tests showed leukopenia and mild anemia. The pathologic result of mediastinal lymph node biopsy was granulomatous lesions; thus, the patient was diagnosed with type II sarcoidosis without glucocorticoid therapy. In the following 2 years, the patient suffered from intermittent fever accompanied by dyspnea, fatigue, occasional cough, less sputum, and apparent weight loss. Abnormal physical examinations included leg ulcers and splenomegaly. Laboratory and physical tests revealed pancytopenia, polyserositis, and enlargement of lymph nodes. The pathological findings of leg ulceration, pleura, and left supraclavicular lymph node all suggested granulomas. Diagnosis, Interventions, and Outcomes It strongly suggested sarcoidosis since tuberculosis, lymphoma, and connective tissue disease were all excluded. Due to severe conditions and multiorgan involvement, we tried to provide methylprednisolone for this patient. After 9 months of oral glucocorticoids therapy, his subjective symptoms as well as hematological and radiological findings were all improved. His leg skin ulceration and scab were also completely disappeared. Conclusion Sarcoidosis has diverse clinical presentations, and many patients present with atypical symptoms. It needs to be timely identified by the clinician and carefully differentiated from other diseases with similar findings so as to make an accurate diagnosis. In this case, the patient had a poor clinical response to glucocorticoids in the early stage of treatment due to the severe condition and multi-organ involvement. It is worth noting that the patient had improved significantly after 9 months of treatment of corticosteroids, which suggested that follow-up is critical.